Glass fiber reinforced nylon composite material and preparation method thereof
By using phosphite antioxidants and maleic anhydride grafted ethylene-octene copolymer elastomers in PA66 materials, combined with glass fiber coupling treatment, glass fiber reinforced nylon with high surface resistivity was prepared. Composite materials solve the problem of the resistivity of PA66 materials in the prior art under boiling environment, and are suitable for the field of railway equipment.
Patent Information
- Application Number
- CN202411540822.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively improve the surface resistivity of PA66 materials in boiling environments, and the impact of antioxidants on material performance is uncertain, resulting in a bottleneck in material performance in the field of railway equipment.
Using phosphite antioxidants with specific structures and maleic anhydride grafted ethylene-octene copolymer elastomers as toughening agents, combined with polyethylene lubricants and saturated carboxylic acid sodium salt nucleating agents, through high-speed mixing and The twin-screw extrusion mechanism is made of glass fiber reinforced nylon composite material, and the surface of the glass fiber is silane coupling.
Significantly improve the surface resistivity of PA66 materials in boiling environments, while maintaining or optimizing their mechanical properties and heat resistance, providing a low-cost and fast solution for railway equipment with strict requirements on electrical and mechanical properties. field.
Smart Images

Figure BDA0005112749650000051 
Figure BDA0005112749650000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nylon composite materials, and particularly relates to a glass fiber reinforced nylon composite material and a preparation method thereof. Background Art
[0002] Polyamide, commonly known as nylon, is a general term for thermoplastic resins containing repeating amide groups — [NHCO] — on the main chain of the molecule, including aliphatic PA, aliphatic-aromatic PA and aromatic PA. Among them, aliphatic PA has many varieties, large output and wide application. Its name is determined by the specific number of carbon atoms in the synthetic monomer. Nylon materials have good mechanical properties, high heat resistance, strong solvent resistance and excellent electrical properties, as well as good barrier properties and self-lubricating properties. These excellent comprehensive properties make nylon materials widely used in automobiles, machinery manufacturing, electronics, railways and other fields; Fiberglass is an inorganic non-metallic material with excellent performance. It comes in many varieties. Its advantages are good insulation, strong heat resistance, good corrosion resistance and high mechanical strength, but its disadvantages are brittleness and poor wear resistance. It is made of six kinds of minerals, namely pyrophyllite, quartz sand, limestone, dolomite, colemanite and magnesia borax, through high temperature melting, wire drawing, winding and weaving. The diameter of its single filament is from several microns to more than 20 microns, which is equivalent to 1 / 20-1 / 5 of a hair. Each bundle of fiber is composed of hundreds or even thousands of single filaments. Glass fiber is usually used as reinforcing material in composite materials, electrical insulation material and thermal insulation material.
[0003] Traditionally, in order to improve the boiling resistance and surface resistivity of PA66 materials, the industry usually adopts methods such as adding fillers, modifiers or surface treatment. Among them, glass fiber reinforcement is one of the effective ways to improve the mechanical properties and heat resistance of PA66, but simple glass fiber reinforcement is often difficult to effectively solve the problem of decreased surface resistivity after boiling. In addition, there are many types of antioxidants on the market, and their effects on the performance of PA66 materials vary. Most of the research focuses on how to improve the material's anti-oxidation and aging performance. There are relatively few studies on how to improve the surface resistivity of PA66 in a boiling environment through the selection of antioxidants. It is currently difficult to quickly and low-costly improve the surface resistivity of PA66 in a boiling environment. Summary of the invention
[0004] The object of the present invention is to provide a glass fiber reinforced nylon composite material and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A glass fiber reinforced nylon composite material comprises the following steps:
[0007] The composite material comprises the following components by weight: 20-60 parts of PA66 resin, 20-50 parts of glass fiber, 1-5 parts of toughening agent, 0.1-1 parts of antioxidant, 0.1-1 parts of lubricant, and 0.1-1 parts of nucleating agent; the toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, and the nucleating agent is a saturated carboxylic acid sodium salt; the viscosity of the PA66 resin is 2.4-2.8, the glass fiber is a short alkali-free glass fiber with a diameter of 10um and a length of 3mm, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0008] Preferably, the composite material comprises the following components by weight: 45-55 parts of the PA66 resin, 30-35 parts of the glass fiber, 2-4 parts of the toughening agent, 0.2-0.5 parts of the antioxidant, 0.2-0.5 parts of the lubricant, and 0.2-0.5 parts of the nucleating agent.
[0009] Preferably, the viscosity of the PA66 resin is 2.7.
[0010] Preferably, the antioxidant has a molecular weight in the range of 500-700 and a melting point in the range of 180-190°C.
[0011] A preparation method of a glass fiber reinforced nylon composite material comprises the following steps: mixing PA66 resin, a toughening agent, an antioxidant, a lubricant and a nucleating agent in a high-speed mixer for 1-2 minutes to obtain a premix, adding the premix to an extruder from a main feeding port, adding glass fiber to the extruder from a side feeding port, and melt-extruding and granulating to obtain the glass fiber reinforced nylon composite material.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] Aiming at the deficiencies in the prior art, the present invention patent found through a large number of experimental screening and comparative analysis that certain antioxidants with special structures can significantly improve the surface resistivity of PA66 materials in a boiling environment, while maintaining or further optimizing its mechanical properties and heat resistance. This discovery provides new ideas and methods for preparing glass fiber reinforced PA66 materials with high surface resistivity. This material not only has a simple preparation process and low cost, but is also more suitable for use in the field of railway equipment that has strict requirements on electrical and mechanical properties, and is expected to solve the long-standing bottleneck problem of material performance in this field. DETAILED DESCRIPTION
[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0015] Embodiment 1:
[0016] A glass fiber reinforced nylon composite material comprises the following components by weight: 45 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.3 parts of antioxidant, 0.3 parts of lubricant and 0.3 parts of nucleating agent.
[0017] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0018] A preparation method of a glass fiber reinforced nylon composite material comprises the following steps: mixing PA66 resin, a toughening agent, an antioxidant, a lubricant and a nucleating agent according to the above weight proportions by using a high-speed mixer, and then adding the mixture into a twin-screw extruder through a main feeding port.
[0019] (screw diameter 35 mm, aspect ratio L / D = 40), glass fiber is added into the twin-screw extruder through the side feed port.
[0020] The temperatures of each barrel of the twin-screw extruder (from the feeding port to the die) are 140°C, 240°C, 250°C, 240°C, 230°C, 220°C, 220°C, 210°C, 220°C, and 230°C respectively.
[0021] The screw speed is 350r / min and the feed rate is 40KG / h.
[0022] The glass fiber reinforced nylon composite material is obtained by extrusion granulation under this condition.
[0023] The product obtained above was placed in an oven for drying (100°C, 3h) and then injection molded to obtain the required test square plate (3mm thick, 8cm long and wide) at a temperature of 250°C. The square plate was left standing for 24 hours at 23°C and 50% relative humidity to test its performance. The performance test results are shown in Table 1.
[0024] The surface resistivity test method is:
[0025] Place a 3mm thick square plate (8cm in length and width) at room temperature for 24 hours, then boil it in a constant temperature water bath at 100℃ for 3 hours, take it out, and wipe the surface dry. Use a superinsulation meter to test the surface resistivity of the material.
[0026] Before and after boiling, the surface of the square plate is cleaned by wiping with anhydrous ethanol to remove surface stains and grease to ensure the accuracy of the test results. During the test, it should be ensured that the probe of the super insulation meter is in good contact with the surface of the square plate to avoid the influence of air gap on the test results. Twin-screw extruder, super insulation meter is a material that can be purchased on the market, such as Beijing Beiguang Precision Instrument BEST-121 digital high resistance meter insulation material surface resistivity tester.
[0027] Embodiment 2:
[0028] A glass fiber reinforced nylon composite material comprises the following components in parts by weight: 50 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.3 parts of antioxidant, 0.3 parts of lubricant and 0.3 parts of nucleating agent.
[0029] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0030] The preparation method is the same as that of Example 1, and the testing method is the same as that of Example 1.
[0031] Embodiment three:
[0032] A glass fiber reinforced nylon composite material comprises the following components by weight: 50 parts of PA66 resin, 33 parts of glass fiber, 2 parts of toughening agent, 0.2 parts of antioxidant, 0.3 parts of lubricant and 0.3 parts of nucleating agent.
[0033] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0034] The preparation method is the same as that of Example 1, and the testing method is the same as that of Example 1.
[0035] Comparative Example 1:
[0036] A glass fiber reinforced nylon composite material, comprising the following components by weight: 50 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.2 parts of antioxidant H10 (Brüggemann Chemicals Co., Ltd.), 0.3 parts of lubricant, and 0.3 parts of nucleating agent.
[0037] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0038] The preparation method is the same as that of Example 1, and the testing method is the same as that of Example 1.
[0039] Comparative Example 2:
[0040] A glass fiber reinforced nylon composite material comprises the following components by weight: 50 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.3 parts of commercially available antioxidant PEP-36, 0.3 parts of lubricant, and 0.3 parts of nucleating agent.
[0041] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0042] The preparation method is the same as that of Example 1, and the testing method is the same as that of Example 1.
[0043] Comparative Example 3:
[0044] A glass fiber reinforced nylon composite material comprises the following components by weight: 50 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.3 parts of antioxidant RIANOX 1098, 0.3 parts of commercially available, 0.3 parts of lubricant, and 0.3 parts of nucleating agent.
[0045] The toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
[0046] The preparation method is the same as that of Example 1, and the testing method is the same as that of Example 1.
[0047] test:
[0048] Table 1 Glass fiber reinforced nylon composite materials and performance tests
[0049]
[0050]
[0051] The antioxidant A used in the comparative example was antioxidant H10, from Brüggemann Chemicals Co., Ltd.;
[0052] The antioxidant B used in the comparative example is antioxidant PEP-36, which is commercially available;
[0053] The antioxidant C used in the comparative example is antioxidant RIANOX1098, which is commercially available;
[0054] It can be seen from Table 1 that compared with Comparative Examples 1-3, Examples 1-3 indicate that a glass fiber reinforced nylon composite material prepared by the antioxidant used in the present invention has a higher surface resistivity than a glass fiber reinforced nylon composite material prepared by other antioxidants.
[0055] In summary, when the composite material is 45 parts of PA66 resin, 35 parts of glass fiber, 2.5 parts of toughening agent, 0.3 parts of antioxidant, 0.3 parts of lubricant, and 0.3 parts of nucleating agent.
[0056] The antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, the nucleating agent is a saturated carboxylic acid sodium salt, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the resistivity of the prepared material is the highest when the silane coupling agent is aminosilane.
[0057] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.
[0058] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A glass fiber reinforced nylon composite material, characterized in that: The composite material comprises the following components by weight: 20-60 parts of PA66 resin, 20-50 parts of glass fiber, 1-5 parts of toughening agent, 0.1-1 parts of antioxidant, 0.1-1 parts of lubricant, and 0.1-1 parts of nucleating agent; the toughening agent is maleic anhydride grafted ethylene-octene copolymer elastomer (POE-g-MAH), the antioxidant is a phosphite antioxidant, the lubricant is a polyethylene lubricant, and the nucleating agent is a saturated carboxylic acid sodium salt; the viscosity of the PA66 resin is 2.4-2.8, the glass fiber is a short-cut alkali-free glass fiber with a diameter of 10um and a length of 3mm, the surface of the glass fiber is treated with a coupling agent, the coupling agent is a silane coupling agent, and the silane coupling agent is aminosilane.
2. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The composite material comprises the following components by weight: 45-55 parts of the PA66 resin, 30-35 parts of the glass fiber, 2-4 parts of the toughening agent, 0.2-0.5 parts of the antioxidant, 0.2-0.5 parts of the lubricant, and 0.2-0.5 parts of the nucleating agent.
3. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The viscosity of the PA66 resin is 2.
7.
4. The glass fiber reinforced nylon composite material according to claim 1, characterized in that: The antioxidant has a molecular weight range of 500-700 and a melting point between 180-190°C.
5. A method for preparing a glass fiber reinforced nylon composite material, characterized in that: The following steps are involved: The PA66 resin, toughening agent, antioxidant, lubricant and nucleating agent are mixed in a high-speed mixer for 1-2 minutes to obtain a premix, the premix is added to the extruder from the main feed port, the glass fiber is added to the extruder from the side feed port, and the glass fiber reinforced nylon composite material is obtained by melt extrusion and granulation.
Citation Information
Cited By
High-strength corrosion-resistant PA66 as well as preparation method and application thereof
CN120842842A
